2004
DOI: 10.1038/nature02667
|View full text |Cite
|
Sign up to set email alerts
|

A high abundance of massive galaxies 3–6 billion years after the Big Bang

Abstract: Hierarchical galaxy formation is the model whereby massive galaxies form from an assembly of smaller units. The most massive objects therefore form last. The model succeeds in describing the clustering of galaxies, but the evolutionary history of massive galaxies, as revealed by their visible stars and gas, is not accurately predicted. Near-infrared observations (which allow us to measure the stellar masses of high-redshift galaxies) and deep multi-colour images indicate that a large fraction of the stars in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
324
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(350 citation statements)
references
References 29 publications
25
324
1
Order By: Relevance
“…Kauffmann et al 2003) and at high redshift (e.g. Glazebrook et al 2004). In addition, Juneau et al (2005) show that the more massive galaxies start to form stars earlier than intermediate and low mass objects.…”
Section: Role Of the Environment On Galaxy Formation And Evolutionmentioning
confidence: 99%
“…Kauffmann et al 2003) and at high redshift (e.g. Glazebrook et al 2004). In addition, Juneau et al (2005) show that the more massive galaxies start to form stars earlier than intermediate and low mass objects.…”
Section: Role Of the Environment On Galaxy Formation And Evolutionmentioning
confidence: 99%
“…[53] analyzed the spectra (obtained with the GMOS multi-slit spectrograph) of 25 galaxies with measured D4000 n and Hδ, in the range 0.6 < z < 1.2 and with masses M > 10 10.2 M ⊙ . Stellar masses have been derived from template fits to the multicolor photometry [54], assuming a Baldry et al (2003) IMF [55]. Masses have been scaled by -0.03 dex to convert them to a Chabrier IMF [42,53].…”
Section: Goods-s Samplementioning
confidence: 99%
“…Many previous works have demonstrated that a substantial fraction (30-50%) of the stellar mass formed between z ∼ 3 and z ∼ 1 (Dickinson et al 2003;Fontana et al 2003Fontana et al , 2004Fontana et al , 2006Glazebrook et al 2004;Drory et al 2004;Rudnick et al 2006;Papovich et al 2006;Yan et al 2006;Pozzetti et al 2007). However, it is still unclear what the major channel for galaxy growth is during this period.…”
Section: Introductionmentioning
confidence: 99%